Impact of Value-Added Services: An Assessment of Satisfaction & Preferences in Nursing Homes & Corporate Hospitals: Examining the Impact of Value-Added Services on Satisfaction and Preferences in Indian Healthcare (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The healthcare market in India is split into five key segments as outlined below Hospitals – Government infrastructure including healthcare centres, district and general hospitals and private hospitals including nursing homes, mid-tier, top-tier, and super specialized establishments. Pharmaceuticals – his includes the manufacture, extraction, processing, purification, and packaging of chemicals to be used as medication. Diagnostic – Comprising of businesses and laboratories that offer analytics or diagnostic services including body fluid analysis. Medical Equipment and Supplies – Including establishments engaged in manufacturing and maintaining medical equipment’s for surgical, dental, ophthalmic, laboratory etc. use. Medical Insurance – Comprising of insurance to cover hospitalization expenses, reimbursements etc.According to Anantha Naik Nagappa, Value Added Services (VAS) in healthcare has become essential due to competition and fragmented services leads to increase in cost. A VAS in healthcare is an integrated approach promising the total healthcare in a cost-effective manner. The reimbursement by third party payer or out of the pocket payment is locking in cheap affordable quality VAS in healthcare.